Discipleship in Systematic Theology: Implications for Soteriology - Milli Rodrigues, Adriani (Kerygma, 2025)
Contrary to the general tendency to overlook discipleship as a prominent topic in the various loci of systematic theology, this article argues that this is a fruitful topic in the context of soteriology, assuming that discipleship is an integral part of the experience of the process of salvation in the development of Christian life. In order to constructively articulate the implications of discipleship for soteriology, this article investigates the concept of discipleship in the NT (the Gospels and Acts) and briefly dialogues with Bonhoeffer’s reflection on discipleship and grace, since it constitutes a relevant example of a systematic articulation between discipleship and soteriology in contemporary theology. Considering the biblical picture of discipleship and Bonhoeffer’s systematic articulation of discipleship and salvific grace, the article depicts the present experience of salvation in terms of a concrete process that involves the life of discipleship, not as a form of salvation by works, but rather as the divine gift of costly grace.